Avoiding the sapling and the elephant: A case study from Uganda of the impact of short-term teams on participants and host communities. Issue 4 (October 2019) - Barr, David
Short-term teams are a growing phenomenon that are gaining increasing attention, with some arguing such trips can create empowered citizens devoted to social justice. But there has also been increasing scrutiny on the impact of such trips on host communities, with questions arising over whether more harm is done than good. This research seeks to contribute to this debate by considering a case study of a short-term team from Ireland which traveled to Uganda, and examining the impact on the participants and host community. It is found that the team is viewed in a positive light by the host community, and with many criticisms of short-term teams not emerging as strongly as the literature suggests, it is postulated this is due to the team characteristics, which could serve as potential guidelines for best practice for other organizations sending short-term teams. Furthermore, recommendations are suggested so implementation can be improved further. However, it is suggested that the negative impacts of short-term teams are too potentially grievous to justify their unchecked proliferation, and that organizations should strongly reconsider sending teams unless they can ensure they are occurring within specific parameters such as those suggested within this research.